Questionnaire Instrument to Measure Elementary Education Teachers' Bullying Awareness - Sa’idah, Nusrotus; Putri, Linda Indiyarti; Rohman, Fathur; Ghoni, Aris Abdul; Farida, Yushinta Eka; Ndayizeye, Oscar (Yayasan Keluarga Guru Mandiri, 2025)
The increasing prevalence of bullying in elementary schools has raised serious concerns regarding the safety and well-being of students. This study aims to develop and validate a theoretically grounded instrument to assess elementary school teachers' awareness of bullying behavior. A total of 121 teachers from Central Java participated as respondents. The instrument was developed based on the Olweus Bullying Questionnaire (OBQ) and the Bullying and Cyberbullying Scale (BCS), covering four key dimensions: bullying detection, behavioral changes, causes of bullying, and preventive actions. Content validity was assessed using Aiken's V analysis, while construct validity was examined through Confirmatory Factor Analysis (CFA), demonstrating a satisfactory model fit (CFI 0.90, RMSEA 0.08). Reliability analysis indicated excellent internal consistency, with Cronbach's ? and McDonald's ? values exceeding 0.90. The findings confirm that the developed instrument is both valid and reliable in measuring teachers' awareness of bullying. This research contributes to the development of assessment tools in education, providing a practical framework for improving teachers' roles in bullying prevention and intervention in elementary schools.